The investigative competence and the use of strategies for its development, in students of initial education of two Peruvian universities - Huaita Acha, Delsi Mariela (2019)
Objective: To know and compare the knowledge of the investigative competence and the use of strategies for its development, in initial education students of two Peruvian universities. Method: Quantitative approach, basic type, descriptive-comparative level. The sample consisted of 28 students in the fifth year of the initial education career of a public and private university. The instruments were checklists that were validated for study purposes. Result: The level of knowledge about the research competence is lower in private university students (57.1%) but the difference with those of the public university is not significant (U = 341,500; p > 0.05). On the other hand, the level of use of strategies to develop research competence in children by private university students tends to be low (71.4%) and in those of the public university it tends to be high (45.2%), There are significant differences in the level of use of these strategies between both universities (U = 217,000; p> 0.05). Conclusion. The two groups of students have low knowledge of the investigative competence, while public university students use strategies more frequently to develop this competence in children. Classroom management in order to get children to focus on the proposed activities seems to be a variable that influences this difference.